Inspecting the Accessibility of Instant Payment Systems from the Perspective of Low Literacy People - Melo, Giselle Lorrane Nobre; Menezes, Nicoly Da Silva; Da Silva, Ingrid Moreira Miranda; Teran, Luciano Arruda; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Digital banking services are embedded in people’s daily lives. Despite this, these services are not accessible to everyone for various reasons, especially for people with low literacy. The objective of this work was to develop a method of accessibility inspection in instant payment services, and the examination was directed toward the public mentioned before. For this reason, an inspection was carried out in five Brazilian banking applications, guided on design considerations based on the literature and case studies applied in the contexts of a riverside community and around elderly people with less experience of digital technology. The results found in the inspection indicate how much the design considerations are satisfied, not satisfied, and partially satisfied in the inspected applications. Additionally, it was possible to review and evaluate design considerations and propose improvements aimed at professionals who intend to develop accessible digital banking services.